2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7592110
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of changes in the electrical properties of novel knitted conductive textiles during cyclic loading

Abstract: Abstract-Combining stainless steel with polyester fibres adds an attractive conductive behaviour to the yarn. Once knitted in such a manner, fabrics develop sensing properties that make the textiles, also known as e-textiles, suitable for smart/wearable applications. Structural deformations of the fibres (e.g. stretching) will cause changes in the conductivity of the fabric. This work investigates changes in the electrical properties exhibited by four knitted conductive textiles made of 20% stainless steel and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…To meet these desired properties, polymers including polytetrafluoroethylene (PTFE) [ 13 ], polyurethane acrylate (PUA) [ 80 ], polydimethylsiloxane (PDMS) [ 81 , 85 , 89 , 100 ], polyimide (PI) [ 82 , 83 ], poly(3,4-ethylenedioxythiophene) (PEDOT) [ 82 , 96 , 99 ], poly(styrenesulfonate) [ 82 ], silicone [ 88 , 90 ], thermoplastic urethane [ 99 , 103 ], ionogels [ 97 ], and hydrogels [ 21 , 91 ], knitted and woven textiles [ 76 , 90 , 95 , 98 , 104 ], overlock stitched textiles [ 78 ], conductive multifilaments that can be incorporated into textiles [ 92 ], polymer coated textiles [ 96 ], sensors embedded in apparel [ 12 ], carbon nanotubes (CNTs) [ 20 , 75 , 77 , 79 , 87 , 93 , 105 ], graphene [ 30 , 84 , 94 , 106 ], or combinations thereof are often used in conjunction with conductive materials.…”
Section: External Wearable Sensing Technologiesmentioning
confidence: 99%
See 3 more Smart Citations
“…To meet these desired properties, polymers including polytetrafluoroethylene (PTFE) [ 13 ], polyurethane acrylate (PUA) [ 80 ], polydimethylsiloxane (PDMS) [ 81 , 85 , 89 , 100 ], polyimide (PI) [ 82 , 83 ], poly(3,4-ethylenedioxythiophene) (PEDOT) [ 82 , 96 , 99 ], poly(styrenesulfonate) [ 82 ], silicone [ 88 , 90 ], thermoplastic urethane [ 99 , 103 ], ionogels [ 97 ], and hydrogels [ 21 , 91 ], knitted and woven textiles [ 76 , 90 , 95 , 98 , 104 ], overlock stitched textiles [ 78 ], conductive multifilaments that can be incorporated into textiles [ 92 ], polymer coated textiles [ 96 ], sensors embedded in apparel [ 12 ], carbon nanotubes (CNTs) [ 20 , 75 , 77 , 79 , 87 , 93 , 105 ], graphene [ 30 , 84 , 94 , 106 ], or combinations thereof are often used in conjunction with conductive materials.…”
Section: External Wearable Sensing Technologiesmentioning
confidence: 99%
“…Most studies that assess the fatigue of wearable stress sensors employ high-amplitude, low-cycle fatigue (LCF) of ≤ 10,000 cycles [ 107 , 108 ] that typically does not result in failure of the sensors [ 1 , 11 , 12 , 13 , 21 , 76 , 78 , 79 , 80 , 81 , 84 , 85 , 87 , 88 , 89 , 90 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 103 , 104 ]; therefore, the number of cycles to failure ( N f ) are unknown. To reiterate, the purpose of such studies is to demonstrate “proof of concept” for a given sensor, not to necessarily identify the mechanical properties of the materials used in the fabrication of the sensor; however, for physiologically based applications, such as cardiovascular monitoring or measuring the typical range of motion for a joint, the sensors need to withstand low-amplitude, high-cycle fatigue (HCF) [ 109 ].…”
Section: External Wearable Sensing Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This research showed that sensors could be used for applications where mechanical movement caused stretching. Other study [14] has been carried out with four knitted conductive textiles during 500 cyclic loadings. It was discovered that after an initial preconditioning round of testing the stabilisation of the electrical behaviour was faster and more repeatable.…”
Section: Introductionmentioning
confidence: 99%